-5x-4=6x-6

Simple and best practice solution for -5x-4=6x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-4=6x-6 equation:



-5x-4=6x-6
We move all terms to the left:
-5x-4-(6x-6)=0
We get rid of parentheses
-5x-6x+6-4=0
We add all the numbers together, and all the variables
-11x+2=0
We move all terms containing x to the left, all other terms to the right
-11x=-2
x=-2/-11
x=2/11

See similar equations:

| Y=2(1.15)x | | 8d-40÷7=-8 | | X/4+7=2x+3 | | x(x^2+7)=1/2(14x^2+16) | | 5y-3y-13=27.64 | | -5x+15=3(11-x) | | -4.5x+1.7=5x+81.5 | | -4(7n-4)=-9(7n+6) | | X-(4x-2)=-10x+23 | | 96.3=9(m+3.8) | | 2x11=7 | | 12x+16x=64 | | 4()3x+1=-2(5x-2) | | 3a+a=1.60 | | 3a=1.60 | | a+a=1.60 | | a4=1.60 | | 6b+4=-2b-16 | | 79.8=7(m+3.6) | | 0=5x^2-7x+9 | | 4a=1.60 | | 10x+13=5x+76.5 | | 3x-13=4(x-4) | | 79.8=7(m+3.6 | | 2(-7x+2)=4 | | -6(2-x)+3(x-4)=12 | | 4y+7+y=10+3y | | s+s=18 | | -282=-6(5+7x) | | n=3•45 | | s/2=18 | | 1800-×=3x |

Equations solver categories